A review on literatures in planning and managing of Islamic wealth distribution (2001-2013) - Muhammad Ridhwan Ab. Aziz; Mohammad Noorizzuddin Nooh; Khairil Faizal Khairi; Fuadah Johari; Mirza A.A.I.; Nordin N.I. (University of Idaho Library, 2024)
Indexed by Scopus